Determination of the relationship between oral-dental health and nutritional status of mentally handicapped individuals - KIRAÇ, SİNEM BÜŞRA; BERKEL, GÜLCAN; İSLAMOĞLU, AYŞE HÜMEYRA; BAYRAM, FERİT; YILDIRIM, HATİCE SELİN; AKTAÇ, ŞULE (My University, 2022)
Objective: Decayed teeth, gum problems, swallowing difficulties, malnutrition and feeding difficulties complicate the life of disabled patients. In this study; It is aimed to determine the oral-dental health and nutritional status of mentally handicapped individuals and to identify possible relationships. Materials-Methods: Mentally disabled individuals (n=23) between the ages of 18-65 who underwent dental treatment at Marmara University Faculty of Dentistry participated in the study. Plaque index (PI), gingival index (GI) and bleeding on probing (SK), oral hygiene habits of the participants, oral health status with community periodontal index of treatment needs (CPITN), DMFT and DMFS, chewing functions and nutritional status were evaluated. Results: The mean age of the individuals participating in the study was 30.04±11.99, of which 11 were male and 12 were female. The mean PI, GI, and SK levels of the individuals were 1.47±0.60, 1.08±0.56, 72.24±13.40%, CPITN, DMFT and DMFS averages were 2.65±0.49, 20.83±7.80, 68.7±33.5 respectively. It was determined that 70.8% of the participants had 3 main meals and 87.5% had at least 1 snack. Meat, fried chicken, peeled apples, raw carrots and nuts were among the foods with the most chewing problems. The body mass index of the female participants was 26.0 kg/m2 on average, and the body mass index of the male participants was 30.8 kg/m2, which was found to be higher than the female participants. Conclusion: It has been observed that increased poor oral-dental health and impaired nutritional status in individuals with mental retardation are closely related to each other and to general health.
Keywords: Nutrition Status; Oral Health; Intellectually Disabled